Storybook as a Preventive Measure Against the "Sexual Harassment" of Children in the Elementary School - Jamain, Ririanti Rachmayanie; Putro, Hendro Yulius Suryo; Hairunisa, Hairunisa; Ariliani, Tiara (International Journal of Asian Education, 2023)
The three great sins of education, bullying, sexual violence and intolerance - still occur in schools. Cases of sexual harassment were found to occur in primary schools. Guidance and counseling are considered the most important parts in this case, where class teachers implement counseling services in primary schools. Sex education can be provided through interesting media. This research aims to produce a learning medium: a storybook about sexual harassment. This research method uses the ASSURE research and development model (Analyze learners, State objectives, select methods, media and materials, utilize media and materials, require learner participation, Evaluate and revise). The research was conducted on students of Grade VI of SDN Sungai Miai 7 Banjarmasin. Material experts, media experts and students as users validated the storybook media. The results showed that the storybook materials met the criteria of being very feasible regarding media and materials and that students' understanding of sexual harassment increased after reading the storybook.